Difusión en interfaces. Sistema Zr-Nb- 1° Parte. - Piotrkowski, Rosa; Dyment, Fanny (Comisión Nacional de Energía Atómica; Argentina, 1985)
Fil: Piotrkowski, Rosa Comisión Nacional de Energía Atómica; Argentina